Optimizing cut-out distance for maximum coal productivity. (June 2019) - Anani, Angelina; Nyaaba, Wedam; Hekmat, Asieh; Córdova, Eduardo A
The need to increase productivity has led to innovations in highly mechanized equipment such as the continuous miner (CM). However, often times the CM is underutilized, resulting in loss of productivity and increased operating cost. The objective of this study is to apply a simulation tool to evaluate if optimizing support systems, such as cut-out distance, fleet size, and panel dimensions, can maximize CM utilization and productivity. Discrete event simulation is used to analyze different cut-out distances for a room and pillar mining system. The results show that an 11-entry panel width with a fleet size of three shuttle cars is optimum for the variable cut-out distances examined. The utilization and production rate also increases by 6% at the maximum cut-out distance.